MATHEMATICAL MODEL AND ALGORITHM FOR CALCULATION OF MANAGEMENT PROCESSES FOR ADVANCED TRAINING OF SPECIALISTS IN THE HYDROPOWER INDUSTRY (American Journal of Technology and Applied Sciences, 2024)
The article deals with the practical issue of managing the educational process on the example of the hydropower industry. A mathematical model of the problem was created using the principle of systematic approach of management theory and the elements of set theory. A calculation algorithm for solving the problem is created, the results of the calculation experiment are presented, and practical recommendations are given.